Forecasting of the gas pumping aggregates technical condition at methods regression analysis of the vibration parameters - Ясиніцький, Е.П.; Налісний, М.Б. (Proceedings of National Aviation University (archive), 2005)
Composition of the regression analysis methods is offered, which applied by authors in special software package. Presented mathematical associations allows to realize automatic rate of gas pumping aggregate remaining resource based on fluctuation of the scalar vibration parameters values.